2023
DOI: 10.20961/placentum.v10i3.58355
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Protein and Fe Intake With The Event of Anemia In Adolescent: Systematic Review

Abstract: <p><strong>Background: </strong>Adolescents are a group that is prone to anemia. Anemia is defined as a lower than normal haemoglobin level. The prevalence of anemia in adolescents in Indonesia is the highest at the age group of 15-24 years, 32%. The most common cause of anemia is lack of nutrients needed for erythrocyte synthesis. Substances that play a role in haemolysis are protein, vitamins (folic acid, vitamin B12, vitamin C and vitamin E), and minerals (Fe and Cu). </p><p>&l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
1
0
Order By: Relevance
“…Iron is a macro mineral that is needed by the body and plays a role in the formation of red blood cells, especially in the synthesis of hemoglobin [122,123]. The results of the iron analysis (Figure 8) showed that the rice analog formulation consisting of different ratios of cassava flour and banana flour had no significant effect (p > 0.05) on iron levels, with the iron levels obtained ranging from 65.87 to 84.32 ppm, with the rice with a ratio of 70%:30% having the highest level.…”
Section: Levels Of Iron (Fe)mentioning
confidence: 99%
“…Iron is a macro mineral that is needed by the body and plays a role in the formation of red blood cells, especially in the synthesis of hemoglobin [122,123]. The results of the iron analysis (Figure 8) showed that the rice analog formulation consisting of different ratios of cassava flour and banana flour had no significant effect (p > 0.05) on iron levels, with the iron levels obtained ranging from 65.87 to 84.32 ppm, with the rice with a ratio of 70%:30% having the highest level.…”
Section: Levels Of Iron (Fe)mentioning
confidence: 99%
“…Iron is a macro mineral that is needed by the body and plays a role in the formation of red blood cells, especially in the synthesis of hemoglobin [126,127]. The results of the iron analysis (Figure 8) showed that the rice analog formulation consisting of different ratios of cassava flour and banana flour had no significant effect (P>0.05) on iron levels, which the iron level obtained ranging from 65.87-84.32 ppm with a ratio of 70%:30% as the highest.…”
Section: Levels Of Iron (Fe)mentioning
confidence: 99%